2021
DOI: 10.1097/mnm.0000000000001447
|View full text |Cite
|
Sign up to set email alerts
|

Baseline 18F-FDG PET textural features as predictors of response to chemotherapy in diffuse large B-cell lymphoma

Abstract: Purpose We sought to investigate the performance of radiomics analysis on baseline 18F-FDG PET/CT for predicting response to first-line chemotherapy in diffuse large B-cell lymphoma (DLBCL). Material and methods Forty-five patients who received first-line rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R-CHOP) chemotherapy for DLBCL were included in the study. Radiomics features and standard uptake value (SUV)-based measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…An indicator of tumor aggressiveness other than SUVmax is the increased genotypic and phenotypic heterogeneity within the tumor, which can be noninvasively quantified with radiomics analysis. We have previously shown that there are strong correlations between the textural features extracted from PET images and the SUVmax values (30). Our findings should be interpreted in the context of several limitations.…”
Section: Discussionmentioning
confidence: 56%
“…An indicator of tumor aggressiveness other than SUVmax is the increased genotypic and phenotypic heterogeneity within the tumor, which can be noninvasively quantified with radiomics analysis. We have previously shown that there are strong correlations between the textural features extracted from PET images and the SUVmax values (30). Our findings should be interpreted in the context of several limitations.…”
Section: Discussionmentioning
confidence: 56%
“…A total of 24 articles on lymphomas were included in this review [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ], 13 of which studying diffuse large B-cell lymphoma (including 2 studies on gastro-intestinal lymphoma), 3 on follicular lymphoma, 3 on Hodgkin’s lymphoma, 2 on mantle cell lymphoma and 3 on other sub-types of lymphoma. 18F-FDG was the only tracer employed and all studies built radiomic models on baseline, pre-treatment PET images, often including clinical parameters and international prognostic indices.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies evaluated the role of PET radiomics and AI analysis in blood malignancies [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Lymphoma radiomics on 18F-FDG PET/CT was more often assessed on patients with DLBCL, in retrospective cohorts and for prognostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has taken a somewhat different approach, evaluating 45 patients receiving R-CHOP (Rituximab+ Cyclophosphamide + Doxorubicin + Vincristine + Prednisone) chemotherapy for DLBCL, evaluating the ability to predict therapy response [40]. Here, the authors concluded that that SUV max and gray level co-occurrence matrix dissimilarity were independent predictors of lesions with incomplete response.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 84% (n=72/88) achieved complete metabolic response (CMR) at end of therapy PET/CT de ned by Deauville score criteria below 4 [34][35][37][38][39][40]…”
mentioning
confidence: 99%